THE IMPLEMENTATION OF TIKTOK AS MEDIA TEACHING TO IMPROVE STUDENTS’ SPEAKING ABILITY - Tri Wahyu, Riswan; Liando, Nihta V. F.; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research has the purpose of improving students’ English pronunciation by using TikTok application as the media. This research is in the form of quantitative which designate the result in the form of numbers tables and charts not in the form of word. The data of this research comes from SMP Negeri 2 Tondano as the population, while focusing on the students of Class IX A which consist of 24 students as the sampling of the research. In administering this research, the researcher used pre-test and post-test design to find out the improvement of students’ pronunciation by using TikTok application as the media. Pre-test and post-test design is considered as the most suitable for this research which aims to find out improvements from students. The result of the study explains that the students made improvements in pronunciation by 41% while using TikTok application as the media for improving their pronunciation in English. It can be concluded that TikTok application can improve students’ pronunciation in English.